2014
DOI: 10.1503/cjs.008113
|View full text |Cite
|
Sign up to set email alerts
|

The effects on oxidative DNA damage of lapa roscopic gastric band applications in morbidly obese patients

Abstract: Background: Obesity may induce oxidative stress, causing oxidative damage of DNA. We examined associations between decreasing serum and urinary 8-hydroxy-2'-deoxyguanosine (8-OHdG) levels and weight loss in morbidly obese patients before and 6 months after laparoscopic adjustable gastric banding (LAGB). Methods:We compared patients who had surgery for morbid obesity with healthy, nonobese controls. Urine and fasting blood samples were collected once from the controls and from the morbidly obese patients before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 22 publications
2
14
0
Order By: Relevance
“…Similarly, high levels of 8-OHdG were detected in the skeletal muscle of overweight patients, suggesting obesity as a contributing factor to increased oxidative stress [51]. In addition, a recent study suggested that DNA damage caused by ROS occurs more frequently in morbidly obese patients than in age-matched, healthy non-obese controls [48].…”
Section: Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, high levels of 8-OHdG were detected in the skeletal muscle of overweight patients, suggesting obesity as a contributing factor to increased oxidative stress [51]. In addition, a recent study suggested that DNA damage caused by ROS occurs more frequently in morbidly obese patients than in age-matched, healthy non-obese controls [48].…”
Section: Groupmentioning
confidence: 99%
“…It is well known that oxidative stress can lead to oxidative DNA damage, causing strand breaks, altered gene expression and ultimately mutagenesis [48]. A recent study showed that both lipid peroxidation and 8-OHdG (8-hydroxydeoxyguanosine, a biomarker for oxidative damage) were positively correlated with BMI, blood pressure, waist/hip circumference and C-reactive protein [49].…”
Section: Groupmentioning
confidence: 99%
“…In addition, data from literature shows that rapid weight loss followed by surgeries for the introduction of gastric banding resulted in a decline in 8-OHdG concentrations excreted in the urine of patients undergoing this procedure 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Although literature requires reviews that directly address the issue of level of education and oxidative stress, different authors have shown a positive correlation between low levels of schooling, smoking, a sedentary lifestyle, low consumption of antioxidant foods, and high levels of oxidative stress 19,11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation